2019
DOI: 10.3390/nu11040820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus plantarum PS128 on Children with Autism Spectrum Disorder in Taiwan: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: This four-week, randomized, double-blind, placebo-controlled study investigated the effects of Lactobacillus plantarum PS128 (PS128) on boys with autism spectrum disorder (ASD) aged 7–15 in Taiwan. All subjects fulfilled the criteria for ASD diagnosis of DSM-V and the Autism Diagnostic Interview-Revised (ADI-R). Questionnaires used for the primary outcome measure include the Autism Behavior Checklist-Taiwan version (ABC-T), the Social Responsiveness Scale (SRS) and the Child Behavior Checklist (CBCL). The Swan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
175
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(191 citation statements)
references
References 84 publications
1
175
2
3
Order By: Relevance
“…In addition, probiotics were reported to exhibit modulatory effects on CNS disorders, including normalization of anxiety and depression-like behaviors [ 35 , 162 ] and reduction of ASD [ 163 ]. A randomized, double-blind, placebo-controlled study reported that the consumption of probiotic L. plantarum PS128 for four weeks significantly improved ASD associated symptoms, comparted with the placebo group [ 164 ]. The probiotic treatment was also significantly improved the brain function in mice with AD model [ 165 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…In addition, probiotics were reported to exhibit modulatory effects on CNS disorders, including normalization of anxiety and depression-like behaviors [ 35 , 162 ] and reduction of ASD [ 163 ]. A randomized, double-blind, placebo-controlled study reported that the consumption of probiotic L. plantarum PS128 for four weeks significantly improved ASD associated symptoms, comparted with the placebo group [ 164 ]. The probiotic treatment was also significantly improved the brain function in mice with AD model [ 165 ].…”
Section: Interaction Of Gut and Nervous System: Gut–brain Axismentioning
confidence: 99%
“…In individuals diagnosed with ASD, there is hyperactivation of a gene that codes for serotonin reuptake transporters (Israelyan & Margolis, 2018). In ASD, clinical studies with probiotic interventions showed promising results including better cognitive development and improvement in the Autism Diagnostic Observation Schedule, widely used to assess the core autism symptomatic behaviors (Adams, Johansen, Powell, Quig, & Rubin, 2011; Grossi, Melli, Dunca, & Terruzzi, 2016; Kaluzna‐Czaplinska & Blaszczyk, 2012; Liu et al, 2019; Parracho et al, 2010; Sanctuary et al, 2019; Santocchi et al, 2016; Shaaban et al, 2018; Tomova et al, 2015; West Md & Roberts, 2013; for a summary, see Table 3). In the field, 95 out of 500 physicians reported using probiotics in treating children with ASD (Golnik & Ireland, 2009).…”
Section: Improving the Intestinal Microbiota Composition As A Supportmentioning
confidence: 99%
“…Multiple studies have reported effects of probiotic treatments on microbiota composition and GI symptoms in ASD children. Although many of these studies did not analyze the behavior of the children, or did not see any improvement after probiotic administration [26,[119][120][121], other studies did report behavioral improvement [122][123][124][125]. In Shaaban et al (2017) [123], 30 children with ASD were given a 3-month, daily treatment with a patented probiotic mixture (composed of strains of the species L. acidophilus, L. rhamnosus and B. longum) which induced an improvement in communication, sociability and cognitive awareness, characterized by a decrease in the ATEC (autism treatment evaluation checklist) score.…”
Section: Clinical Studiesmentioning
confidence: 99%